2017
DOI: 10.1186/s40738-017-0037-x
|View full text |Cite
|
Sign up to set email alerts
|

Alcohol and fertility: how much is too much?

Abstract: Alcohol use is prevalent in the United States. Given that a substantial portion of the drinking population is of reproductive age, it is not uncommon for couples who are attempting conception, or for women who are already pregnant, to be regularly consuming alcohol. Alcohol use is associated with multiple reproductive risks, including having a child with a Fetal Alcohol Spectrum Disorder, increased risk of fetal loss, and decreased chance of live birth. This review serves to examine the risks of alcohol in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
32
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(39 citation statements)
references
References 55 publications
0
32
0
1
Order By: Relevance
“…On the other hand, the effects of low to moderate consumption of alcohol do not appear to be clinically significant. Several studies have shown no effect in semen parameters with moderate alcohol consumption (Stutz et al 2004, Van Heertum & Rossi 2017. de Jong et al (2014) failed to show a significant relationship between alcohol consumption and not only sperm parameters but also pregnancy outcome.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…On the other hand, the effects of low to moderate consumption of alcohol do not appear to be clinically significant. Several studies have shown no effect in semen parameters with moderate alcohol consumption (Stutz et al 2004, Van Heertum & Rossi 2017. de Jong et al (2014) failed to show a significant relationship between alcohol consumption and not only sperm parameters but also pregnancy outcome.…”
Section: Introductionmentioning
confidence: 99%
“…Numerous studies have shown the deleterious effects of chronic heavy alcohol consumption on testicular function and spermatogenesis (Shayakhmetova et al 2013(Shayakhmetova et al , 2014, on testosterone serum levels (Salonen et al 1992, Muthusami & Chinnaswamy 2005, Lee et al 2010, Jensen et al 2014, Sliwowska et al 2016) and on hypothalamic-pituitary-testicular axis function (Cicero & Badger 1977, Dees et al 1990, Välimäki et al 1990, Salonen et al 1992, Zhang et al 2005. Clinical manifestations in alcoholic men include hypogonadism, testicular atrophy, feminization, sexual dysfunction (Van Thiel et al 1990, Van Heertum & Rossi 2017, infertility and delayed sexual maturation (Anderson et al 1989). Many studies have suggested that one of the most important negative effects of chronic alcohol ingestion occur in sperm parameters (Rahimipour et al 2013,Condorelli et al 2015.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Other direct effects of alcohol on the female endocrine system have been reported (Rachdaoui and Sarkar 2017), resulting in irregular menstrual/estrous cycles, anovulation, early menopause and elevated estradiol (E2) levels in both women and rodents. High alcohol consumption has also been suggested to negatively impact on assisted reproductive outcomes, with reduced oocytes retrieved, lower rates of pregnancy and increased risk for miscarriage (see Van Heertum and Rossi (2017) for review).…”
Section: Introductionmentioning
confidence: 99%
“…However, there is always the possibility of premature birth, low birth weight, birth defects, infant death, and abortion (5). According to previous studies, there are various reasons for the loss of the pregnancy, such as endocrine causes (e.g., luteal phase defects (6), diabetes (7), hypothyroidism (8), and polycystic ovaries (9)), infectious causes (10), anatomical defects of the uterus (11), environmental causes (e.g., smoking (12), alcohol consumption (13), air pollution (14), and excessive coffee consumption (15)), and old age of parents (4,16,17). In infertility centers, only the medically known factors are considered and examined in infertile couples and in many cases, despite the elimination of all barriers to fertility and the use of pharmacological and invasive methods, the success rate of fertility is still very low.…”
Section: Introductionmentioning
confidence: 99%